1998
DOI: 10.1046/j.1365-3156.1998.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection in tropical and developing countries

Abstract: SummaryLittle is known about the epidemiology of respiratory syncytial virus (RSV) infection in tropical and developing countries; the data currently available have been reviewed. In most studies, RSV was found to be the predominant viral cause of acute lower respiratory tract infections (ALRI) in childhood, being responsible for 27-96% of hospitalised cases (mean 65%) in which a virus was found. RSV infection is seasonal in most countries; outbreaks occur most frequently in the cold season in areas with tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

42
233
5
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(298 citation statements)
references
References 73 publications
(134 reference statements)
42
233
5
10
Order By: Relevance
“…In regions with tropical and sub-tropical climates, the disease appears to be more prevalent in the rainy seasons. 3,14 Although uncommon, the yearly distribution of RSV found in our study has also been described in two other studies. 15,16 Similarly, the beginning of an epidemic during the summer was also reported in the border state of Rio de Janeiro 10 and in Louisiana in the United States.…”
supporting
confidence: 89%
“…In regions with tropical and sub-tropical climates, the disease appears to be more prevalent in the rainy seasons. 3,14 Although uncommon, the yearly distribution of RSV found in our study has also been described in two other studies. 15,16 Similarly, the beginning of an epidemic during the summer was also reported in the border state of Rio de Janeiro 10 and in Louisiana in the United States.…”
supporting
confidence: 89%
“…Singapore is a well known exception to the general finding that peak RSV incidence occurs in the rainy season in tropical settings 4,22 , and consistent with this, both of Singapore studies found a negative association between RSV incidence and relative humidity. More detailed examination of such exceptions would be useful to investigate different environmental and behavioural factors that influence RSV incidence.…”
Section: Discussionmentioning
confidence: 66%
“…Even of the true pneumonias some will be viral, including the vaccine-preventable RSV pneumonias, where antibiotics will make little positive impact on outcome [23,24]. In addition, studies of the quality of care suggest that IMCI procedures to diagnose pneumonia, in particular examining the chest and recording respiratory rate, are not well undertaken outside research settings [25,26].…”
Section: Discussionmentioning
confidence: 99%